Being Christian in Vandal Africa: the politics of orthodoxy in the Post-Imperial West - Whelan, Robin (University of California Press, 2018)
"Being Christian in Vandal Africa investigates conflicts over Christian orthodoxy in the Vandal kingdom--the successor to Roman rule in North Africa, ca. 439 to 533 CE. Exploiting neglected texts, author Robin Whelan exposes a sophisticated culture of disputation between Nicene ("Catholic") and Homoian ("Arian") Christians and explores their rival claims to political and religious legitimacy. These contests--sometimes violent--are key to understanding the wider and much-debated issues of identity and state formation in the post-imperial West."--Provided by publisher